Model Pengembangan Lembaga Penyiaran Publik Lokal (LPPL) Radio di Jawa Tengah - Wiratmo, Liliek Budiastuti; Irfan, Noor; Samudi, Samudi (Jurnal The Messenger, 2016)
Local  Public  Broadcasting  radio  is  broadcasting  reform  that  seeks  to  restore  the  sovereignty of the people as the owners of the frequencies through Act No. 32 of 2002 on Broadcasting.   Government Regulation  No. 11/2005 create the space   to  Local Government Radio Broadcasting can adjust to the regulations on LPPL Radio. However, up to ten years since the birth of the Broadcasting Act, the presence of LPPL Radio presence in Central Java has not been fully able to show a real role. This study used a qualitative approach through bencmarking studies between LPPL radio with the Broadcasting Licence and the Broadcasting Operation Principle Permit, which is Radio Swara Kendal FM; Radio Kota Batik, Pekalongan; Radio Singosari, Brebes; In FM Radio, Kebumen; Irama FM Radio, Purworejo and LPP RRI Semarang. The result of this research is the Local Public Broadcasting Radio development model accordance with applicable regulations.